Arbitration: Nature and Definition - Castillo Freyre, Mario (2006)
Society has witnessed the progressive transformation that justice has undergone over time. In this new landscape, alternative ways of resolving disputes have emerged that go beyond the courts, such as arbitration. Although arbitration has distinctive characteristics that differentiate it from conventional dispute resolution, the authors point out that this type of administration of justice cannot be judged without knowing its history, its purpose and how it actually works. It is not, therefore, a "heresy" in the evolution of law. To that extent, this article deals with the conceptualisation of arbitration, but not before having analysed its nature. In this way, this text allows us to explore and understand arbitration in order to be able to define it correctly and thus discover that it is not a threat, but rather a legitimate and efficient alternative for resolving conflicts in today's society.